Prospect of in vitro Bile Fluids Collection in Improving Cell-Based Assay of Liver Function - Rizki-Safitri, Astia; Tokito, Fumiya; Nishikawa, Masaki; Tanaka, Minoru; Maeda, Kazuya; Kusuhara, Hiroyuki; Sakai, Yasuyuki (Frontiers in Toxicology, 2021)
The liver plays a pivotal role in the clearance of drugs. Reliable assays for liver function are crucial for various metabolism assays, including toxicity, disease, and pre-clinical testing for drug development. Bile is an aqueous secretion of a functioning liver. Analyses of bile are used to explain drug clearance and related effects and are thus important for toxicology and pharmacokinetic research. Bile collection is extensively performed in vivo, whereas this process is hardly reproduced as in the in vitro studies. The key to success is the technology involved, which needs to satisfy multiple criteria. To ensure the accuracy of subsequent chemical analyses, certain amounts of bile are needed. Additionally, non-invasive and continuous collections are preferable in view of cell culture. In this review, we summarize recent progress and limitations in the field. We highlight attempts to develop advanced liver cultures for bile collection, including methods to stimulate the secretion of bile in vitro. With these strategies, researchers have used a variety of cell sources, extracellular matrix proteins, and growth factors to investigate different cell-culture environments, including three-dimensional spheroids, co-cultures, and micro-fluidic devices. Effective combinations of expertise and technology have the potential to overcome these obstacles to achieve reliable in vitro bile assay systems.